Characterization of powder apparent viscosity: A reapplication of the Poiseuille equation to silo discharges. (January 2023) - Lu, Haifeng; Zhang, Liang; Guo, Xiaolei; Liu, Haifeng; Cao, Jiakun; Zhu, Lizhuo; Xu, Chunhui
Highlights: This paper provides a new method for powder apparent viscosity characterization. The Poiseuille equation is introduced and modified for silo discharge of powders. The shear-thinning characteristics of powders in silo discharge is found. Reasonable agreements of powder apparent viscosity characterization results are found. Abstract: In the present work, a new method to characterize powder apparent viscosity was proposed by applying the Poiseuille equation to silo discharges. Flow properties of powders were first identified in terms of angle of repose and Hausner ratio, based on which experimental materials were classified as free-flowing and cohesive powders. These powders were further discharged from the pressurized silo, and an exponential increase in the powder discharge rate on the pressure difference was obtained. A model to predict the apparent viscosity was further developed grounded on the Poiseuille equation. The apparent viscosity of both free-flowing and cohesive powders decreases with an increasing flow rate within a specific range, showing the characteristic of shear-thinning. There was a reasonable agreement of powder apparent viscosity characterization between results from the silo discharge and those obtained from the FT4 rheometer, thus, confirming the method's reliability. The new method presented reliable values and had a wide testing range, providing an alternative way to measure powder rheological parameters. Graphical abstract: Image, graphical abstract